Socio-psychological mediators of the relationship between behavioral health stigma and psychiatric symptoms. (May 2017) - Hunter, Bronwyn A.; Mohatt, Nathaniel Vincent; Prince, Dana M.; Thompson, Azure B.; Matlin, Samantha L.; Tebes, Jacob Kraemer
Abstract: The stigma associated with mental illness or addiction is significantly and positively related to psychiatric symptoms. According to Modified Labeling Theory, several processes should mediate this relationship, including rejection experiences, stigma management (secrecy coping), and social support. In the first comprehensive test of this theory, we examined a serial mediation model on three waves of data from 138 adults receiving outpatient behavioral health treatment. Participants were recruited from outpatient behavioral health clinics in a large northeastern city in the United States and completed interviews that assessed stigma, rejection experiences, stigma management, social support, and psychiatric symptoms. There was a direct effect between stigma and psychiatric symptoms and an indirect effect in which perceived rejection, secrecy coping and social support sequentially and longitudinally intervened in the stigma and psychiatric symptom relationship. Higher perceptions of stigma predicted more rejection experiences, which marginally increased secrecy coping and decreased social support. In turn, decreased social support increased psychiatric symptoms. We provide support for Modified Labeling Theory and the clinical utility of specific mediators in the relationship between stigma and psychiatric symptoms among adults in behavioral health treatment living in urban settings. Highlights: The stigma of mental illness and/or addiction negatively affects psychiatric symptoms. Modified Labeling Theory specifies socio-psychological processes that mediate stigma and symptoms. These processes include rejection experiences, secrecy coping and social support. This study is the first comprehensive longitudinal test of Modified Labeling Theory. Results support the theory, and suggest how to address the stigma–symptom relationship.